Impact of a specialty pharmacy benefit on rheumatoid arthritis medication adherence and functional status: a continuation study. (3rd September 2019) - Kozlicki, Miranda; Zande, Marc; Wickizer, Marleen; Topp, Robert; Faust, Sharon; Hustad, Chelsea
Abstract: Background: Patients with rheumatoid arthritis (RA) have benefited from the introduction of tumor necrosis factor (TNF) inhibitors; however, multiple studies have reported that rates of medication adherence are sub-optimal. Specialty pharmacies offer various management strategies to improve adherence in patients with RA to help improve disease status. Aims: To expand the initial analysis results by gathering adherence data between 6 and 12 months and HAQ-II scores at 12 months after transitioning members to the specialty pharmacy to determine the impact of a specialty pharmacy benefit on RA medication adherence and functional status. Methods: A retrospective analysis was conducted using an internal pharmacoadherence application. Members with claims for TNF-inhibitors were included, provided they received at least two fills within the study time periods of May 1, 2017–December 31, 2017 (pre-transition), January 1, 2018–August 31, 2018 (post-transition), and September 1, 2018–April 30, 2019 (extension). Pharmacy claims were analyzed to measure adherence by calculating the proportion of days covered (PDC) in each time period. Members with a baseline HAQ-II score after transition were compared to 6-month post-transition and 12-month extension HAQ-II scores for a correlation to adherence. Results: A total of 101 members with RA were included. Prior to transition, 34% of members were filling at non-specialty pharmacies and 66% of members were filling at specialty pharmacies. PDC values for baseline, post-transition, and extension time periods were 0.848, 0.907, and 0.819, respectively, for members filling at non-specialty pharmacies prior to transition and 0.904, 0.889, and 0.818, respectively, for members filling at a specialty pharmacy prior to transition. The percentage of patients achieving a desired adherence level (PDC>0.8) increased post-transition for members previously filling at non-specialty pharmacies (65.2% vs 84.8%). A statistically significant inverse relationship was found between baseline HAQ-II score and pre-transition PDC value ( r = –0.200, p  = .035) for 112 members with completed functional assessments. Conclusions: PDC is significantly correlated to HAQ-II scores at baseline, and adherence is also shown to increase for members transitioning from a non-specialty to specialty pharmacy. More analysis is needed to determine if the HAQ-II is an appropriate functionality questionnaire to assess RA disease status.